How may two C# Lambda Expressions be combined without using an invoke?

c# entity-framework lambda linq-to-entities

Question

I'd like to merge the following Expressions:

// example class
class Order
{
    List<OrderLine> Lines       
}
class OrderLine { }

Expression<Func<Order, List<OrderLine>>> selectOrderLines = o => o.Lines;
Expression<Func<List<OrderLine>, Boolean>> validateOrderLines = lines => lines.Count > 0;

// now combine those to
Expression<Func<Order, Boolean>> validateOrder;

I got it to work using a invoke on the selectOrderLines and supplying the result to the validateOrderLines, but because I'm using these expressions in Entity Framework, I have to actually create a clean expression which should represent:

Expression<Func<Order, Boolean>> validateOrder = o => o.Lines.Count > 0;

How can I do this?

1
12
3/28/2015 7:24:53 PM

Accepted Answer

The most elegant way is to use an Expression Visitor. In particular, this MSDN Blog Entry describes how to use it to combine predicates (using boolean And or Or) without Invoke.

EDITED Having realized boolean combination is not what you wanted, I wrote a sample usage of ExpressionVisitor that solves for your particular problem:

public class ParameterToMemberExpressionRebinder : ExpressionVisitor
{
    ParameterExpression _paramExpr;
    MemberExpression _memberExpr;

    ParameterToMemberExpressionRebinder(ParameterExpression paramExpr, MemberExpression memberExpr) 
    {
        _paramExpr = paramExpr;
        _memberExpr = memberExpr;
    }

    protected override Expression Visit(Expression p)
    {
        return base.Visit(p == _paramExpr ? _memberExpr : p);
    }

    public static Expression<Func<T, bool>> CombinePropertySelectorWithPredicate<T, T2>(
        Expression<Func<T, T2>> propertySelector,
        Expression<Func<T2, bool>> propertyPredicate)
    {
        var memberExpression = propertySelector.Body as MemberExpression;

        if (memberExpression == null)
        {
            throw new ArgumentException("propertySelector");
        }

        var expr = Expression.Lambda<Func<T, bool>>(propertyPredicate.Body, propertySelector.Parameters);
        var rebinder = new ParameterToMemberExpressionRebinder(propertyPredicate.Parameters[0], memberExpression);
        expr = (Expression<Func<T, bool>>)rebinder.Visit(expr);

        return expr;
    }

    class OrderLine
    {
    }

    class Order
    {
        public List<OrderLine> Lines;
    }

    static void test()
    {
        Expression<Func<Order, List<OrderLine>>> selectOrderLines = o => o.Lines;
        Expression<Func<List<OrderLine>, Boolean>> validateOrderLines = lines => lines.Count > 0;
        var validateOrder = ParameterToMemberExpressionRebinder.CombinePropertySelectorWithPredicate(selectOrderLines, validateOrderLines);

        // validateOrder: {o => (o.Lines.Count > 0)}
    }
}
21
7/15/2009 4:19:39 PM

Popular Answer

This extension works:

public static class Utility
    {
        public static Expression<T> Compose<T>(this Expression<T> first, Expression<T> second, Func<Expression, Expression, Expression> merge)
        {
            // build parameter map (from parameters of second to parameters of first)
            var map = first.Parameters.Select((f, i) => new { f, s = second.Parameters[i] }).ToDictionary(p => p.s, p => p.f);

            // replace parameters in the second lambda expression with parameters from the first
            var secondBody = ParameterRebinder.ReplaceParameters(map, second.Body);

            // apply composition of lambda expression bodies to parameters from the first expression 
            return Expression.Lambda<T>(merge(first.Body, secondBody), first.Parameters);
        }

        public static Expression<Func<T, bool>> And<T>(this Expression<Func<T, bool>> first, Expression<Func<T, bool>> second)
        {
            return first.Compose(second, Expression.And);
        }

        public static Expression<Func<T, bool>> Or<T>(this Expression<Func<T, bool>> first, Expression<Func<T, bool>> second)
        {
            return first.Compose(second, Expression.Or);
        }
    }

Sample using:

Expression<Func<Product, bool>> filter1 = p => a.ProductId == 1;
Expression<Func<Product, bool>> filter2 = p => a.Text.StartWith("test");
Expression<Func<Product, bool>> filterCombined = filter1.And(filter2);


Related Questions





Related

Licensed under: CC-BY-SA with attribution
Not affiliated with Stack Overflow
Licensed under: CC-BY-SA with attribution
Not affiliated with Stack Overflow